(untitled) (The Conference Hub, 2025)
Differences in susceptibility and mortality rates between men and women due to COVID-19 have been recorded. Early reports from China indicated a higher prevalence of COVID-19 cases among men (with a male-to-female ratio of 1.27:1), along with an increased mortality rate. Studies conducted in South Korea and the United States reported a higher infection rate among women. However, other studies did not identify significant gender-based differences. Research in the United States highlighted a higher severity of COVID-19 outcomes and mortality rates among men. These findings were later confirmed, showing that men were more frequently hospitalized, admitted to intensive care units (ICUs), intubated, and prescribed vasopressors. These differing results may be attributed to variations in sample sizes, inclusion criteria, and methodological approaches. Large-scale studies incorporating data from multiple countries have confirmed the existence of gender differences in both COVID-19 incidence and mortality.